Negative impact of mild arid conditions in natural rodent populations revealed using markers of physiological condition in natura - Keilani, Hamilcar; Avenant, Nico; Caminade, Pierre; Pillay, Neville; Ganem, Guila (Peer Community Journal, 2025)

(untitled)
Understanding how organisms respond to seasonal variations in their environment can be a window to their potential adaptability, a classical problem in evolutionary ecology. In the context of climate change, inducing increased aridity and disruption of seasonality, it is crucial to study the extent and limits of species responsiveness. Here, the physiological response to food and water shortage during seasonally dry conditions were investigated. We studied populations of two rodent species of the genus Rhabdomys, one arid and one mesic, in a semi-arid zone where their range overlap in South Africa. We measured blood concentrations of markers of kidney and liver function, as well as body condition, at the onset and the end of the dry season. We found similar shifts in blood metabolite levels, in the semi-arid populations of the two species, indicating malnutrition consistent with the observed degradation of habitat quality between the start and the end of the dry season. Furthermore, regardless of the period, differences between the two species in blood metabolite concentrations (e.g. amylase, sodium, alkaline phosphatase) were observed, suggesting contrasting diets and water conservation abilities. Overall, we show that, as seasonal dry conditions worsen, organisms are increasingly affected by reduced food availability, and local adaptation to arid conditions may provide the arid species with an advantage to cope with semi-arid conditions. Our study suggests that even mild arid conditions could have a negative impact and questions resilience of animals to harsher arid conditions.